Prevalence of cervical intraepithelial lesions and associated factors among women attending a cervical cancer clinic in Western Uganda; results based on Pap smear cytology - Ssedyabane, Frank; Niyonzima, Nixon; Najjuma, Josephine Nambi; Birungi, Abraham; Atwine, Raymond; Tusubira, Deusdedit; Randall, Thomas C; Castro, Cesar M; Lee, Hakho; Ngonzi, Joseph (SAGE Open Medicine, 2024)
Introduction: There are high incidence and mortality rates of cervical cancer among females in East Africa. This is exacerbated by limited up-to-date data on premalignant lesions and associated factors in this setting. In this study, we determined the prevalence of cervical intraepithelial lesions and associated factors among women attending the Mbarara Regional Referral Hospital cervical cancer clinic in Southwestern Uganda. Methods: In this cross-sectional study, 364 participants were recruited from among women attending the Mbarara Regional Referral Hospital cervical cancer clinic from 1 April to 30 June 2023. On consent, the study nurse collected demographic data and Pap smears, which were microscopically examined and reported by a laboratory scientist and a pathologist following the Bethesda grading system (2014). Statistical analyses were done in STATA version 17, using proportions, Chi-square, bivariate, and multivariate logistic regression analysis to determine associated factors at ⩽0.05 significance level. Results: The mean age of participants was 41.9 years. A third of all study participants (37.6%, 132/351) were contraceptive users, mostly hormonal contraceptives (87.1%, 115/132). Almost 88% (307/351) had an unknown Human Papilloma Virus status. The prevalence of cervical intraepithelial lesions among our study participants was 6.6% (23/351), of which 73.9% (17/23) were low-grade squamous intraepithelial lesions. More than half (9/17, 52.9%) of low-grade squamous intraepithelial lesions were active hormonal contraceptive users. Use of hormonal contraceptives (OR: 3.032, p: 0.0253), use of intrauterine devices (OR: 6.284, p: 0.039), and any family history of cervical cancer (OR: 4.144, p: 0.049) were significantly associated with cervical intraepithelial lesions. Conclusion: The prevalence of cervical intraepithelial lesions was 6.6%, lower than global estimates. Use of hormonal and intrauterine device contraceptives, as well as family history of cervical cancer, were significantly associated with cervical intraepithelial lesions among our study population. Prospective studies are recommended to further understand associations between different types of intrauterine devices and hormonal contraceptives, and cervical lesions.
Keywords: Cervical intraepithelial neoplasia; Risk factors; Cervical cancer; LSIL; HSIL; ASCUS; Uganda